Application of the joint discrete hadamard-inverse Fourier transform in a MC-CDMA wireless communication system-performance and complexity studies. - Bogucka, H. (IEEE Transactions on wireless communications)
An efficient low-complexity algorithm proposed earlier by the same author is considered for the application in multicarrier radio communication systems with code-division multiple access. An inverse algorithm is proposed as a method of joint detection (JD), which is capable of rejecting intersymbol and multiple-access interference at a reasonable complexity. Computational complexity calculations as well as recent performance results of the proposed method are provided. The bit-error rate performance achieved by the simulated JD algorithms and equalizer structures is comparable with the performance of other methods which exhibit higher complexity.